PECULIARITIES OF SOCIO-POLITICAL LEXICAL ACTIVITY IN LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The specificity of socio-political lexical activity in language is largely determined by strong extralinguistic connections with the nominated events of objective reality. Therefore, the best way to systematize the identified socio-political dictionary and then express it is to present it in the form of interrelated thematic groups.